Comparative Harm, Creation and Death. Issue 2 (27th July 2015) - FEIT, NEIL
Abstract : Given that a person's death is bad for her, when is it bad? I defend subsequentism, the view that things that are bad in the relevant way are bad after they occur. Some have objected to this view on the grounds that it requires us to compare the amount of well-being the victim would have enjoyed, had she not died, with the amount she receives while dead; however, we cannot assign any level of well-being, not even zero, to a dead person. In the population ethics literature, many philosophers have argued along similar lines that bringing someone into existence can neither harm nor benefit her. Working within the comparative framework (on which harms make us worse off), I respond by proposing a good sense in which we can say that dead people, and actual people at alternatives in which they do not exist, have a well-being level of zero.